The Effect of Educational Financing on Lecturer Performance in the Implementation of the Tridharma: An Explanatory Sequential Study at Private Islamic Higher Education Institutions - Baidowi, Ach.; Zebua, Syukurman; Mujahidin, Irfan; Mokhtar, Wan Khairul Aiman Wan; Ma'ruf, Chasan (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
Lecturer performance is strongly influenced by higher education financing, including salaries, allowances, professional training, and research support, which together affect motivation, productivity, and the implementation of the university’s tridharma: teaching, research, and community service. Yet prior studies have not fully examined how implementing higher education financing standards affects lecturer performance in private Islamic higher education institutions, particularly through a mixed-methods, multisite approach. This study analyzes the effect of higher education financing standards on lecturer performance in this context. Using a mixed-methods explanatory sequential design, quantitative data were collected from 95 lecturers via structured questionnaires and analyzed with Smart PLS 4.1 to assess structural relationships. Qualitative data were then gathered through in-depth interviews, document reviews, and observations, and analyzed using a three-stage multisite analysis to contextualize the quantitative findings. Results show that higher education financing significantly and positively influences lecturer performance, explaining 26% of the variance (T = 6.035; p = 0.000; R² = 0.260). Lecturers receive monthly salaries, structural allowances, and fully funded certification and training, while research, community service, publications, and seminar participation are supported in accordance with institutional capacity, with international-oriented activities fully funded. In conclusion, comprehensive and well-structured financing is crucial for enhancing lecturer performance, academic productivity, and institutional reputation, providing policymakers with evidence to design effective, equitable, and sustainable higher education financing policies